Dhammapada: Pali Text and Translation with Stories in Brief and Notes - Narada Thera; THERA (Narada) (Taiwan The Corporate Body of the Buddha Educational Foundation, 1993)
The Dhammapada consists of 423 melodious Pali verses, uttered by the Buddha in the course of His preaching tours during His ministry of forty-five years. It illustrates the moral and philosophical teachings of the Buddha.
Keywords: Pali Alphabet; Buddhism